2017
DOI: 10.1039/c6nr07560f
|View full text |Cite
|
Sign up to set email alerts
|

A classical description of subnanometer resolution by atomic features in metallic structures

Abstract: Recent experiments have evidenced sub-nanometer resolution in plasmonic-enhanced probe spectroscopy. Such a high resolution cannot be simply explained using the commonly considered radii of metallic nanoparticles on plasmonic probes. In this contribution the effects of defects as small as a single atom found on spherical plasmonic particles acting as probing tips are investigated in connection with the spatial resolution provided. The presence of abundant edge and corner sites with atomic scale dimensions in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
122
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 42 publications
7
122
0
Order By: Relevance
“…When compressing the film at low pressure,aface-to-face stacking structure could be formed, and uniform hexagonal pores with as ize of circa 24.7 are expected ( Figure 1D). Note that this additional water layer could act as an insulating layer between the compound 1 ML and the Au(111) surface,w hich avoids interferences from moleculesubstrate interactions and makes for areasonable system for studying intermolecular interactions by TERS.A ccording to recent work, [22] the radius of the TERS enhanced region can be considerably smaller that the radius of the TERS probe. Note that this additional water layer could act as an insulating layer between the compound 1 ML and the Au(111) surface,w hich avoids interferences from moleculesubstrate interactions and makes for areasonable system for studying intermolecular interactions by TERS.A ccording to recent work, [22] the radius of the TERS enhanced region can be considerably smaller that the radius of the TERS probe.…”
mentioning
confidence: 95%
“…When compressing the film at low pressure,aface-to-face stacking structure could be formed, and uniform hexagonal pores with as ize of circa 24.7 are expected ( Figure 1D). Note that this additional water layer could act as an insulating layer between the compound 1 ML and the Au(111) surface,w hich avoids interferences from moleculesubstrate interactions and makes for areasonable system for studying intermolecular interactions by TERS.A ccording to recent work, [22] the radius of the TERS enhanced region can be considerably smaller that the radius of the TERS probe. Note that this additional water layer could act as an insulating layer between the compound 1 ML and the Au(111) surface,w hich avoids interferences from moleculesubstrate interactions and makes for areasonable system for studying intermolecular interactions by TERS.A ccording to recent work, [22] the radius of the TERS enhanced region can be considerably smaller that the radius of the TERS probe.…”
mentioning
confidence: 95%
“…[18] Interestingly,d espite the approximately 30 nm curvature radius of the TERS probe apex, the fiber characterization could be obtained with al ateral spatial resolution lower than 10 nm ( Figures S2 and S3);t his is probably because of the roughness of the metal coating and the formation of ametal nanoparticle at the apex, which is in line with recent reports where the possibility to reach subnanometer resolution was even demonstrated in the presence of defects at the noble metal tip end. [20] The geometry and the electromagnetic properties of this nanoparticle defines its TERS activity,which may change from one TERS probe to another. This dependence,i na ddition to the sensitivity of TERS signals to molecular orientation and gradient-field effects,e xplains the plethora of TERS signatures with variable intensities reported for protein (amyloid especially) fibers described in the literature, [18,[21][22][23][24][25] and for K18 + POPC:PIP 2 and K18 + HS fibers in this study.Because of this intrinsic intensity variability of TERS bands,areliable comparison between TERS features identifiable in the two samples often requires the statistical investigation of their relative abundance in the spectra.…”
mentioning
confidence: 99%
“…Thus, it has been recently shown that sub-nanometric inhomogeneities in field-enhancement patterns in plasmonic gaps [24][25][26] can be described, at least qualitatively, through classical optics calculations. On the other hand, the physical mechanisms behind the failure of classical predictions for the LSPR frequencies in compact nanoparticles (with sizes in the ∼ 1-3 nm range) are well understood.…”
mentioning
confidence: 99%